EVALUATION OF ADJUVANT RADIOTHERAPY OUTCOMES IN STAGE I–III BREAST CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical outcomes of adjuvant radiotherapy in patients with stage I–III breast cancer treated at Nghe An Oncology Hospital.Methods: This retrospective longitudinal descriptive study included 91 patients with stage I–III breast cancer who received adjuvant radiotherapy at Nghe An Oncology Hospital between January and December 2020. Clinical characteristics, treatment outcomes, survival, treatment-related toxicities, and prognostic factors were analyzed.Results: The mean age of the study population was 51.66 ± 11.41 years. Stage I, II, and III disease accounted for 3.3%, 69.2%, and 27.5% of patients, respectively. The rates of locoregional recurrence, distant metastasis, and absence of recurrence or metastasis were 4.4%, 15.4%, and 80.2%, respectively. The 3-year locoregional recurrence-free survival (LRRFS), disease-free survival (DFS), and overall survival (OS) rates were 96.4%, 77.8%, and 84.5%, respectively, while the corresponding 5-year rates were 95.0%, 70.1%, and 74.5%. Late radiation-related toxicities were infrequent and predominantly mild, with lymphedema occurring in 5.49%, radiation-induced pulmonary fibrosis in 12.08%, and chest wall fibrosis in 2.19% of patients. Disease stage was an independent prognostic factor for disease-free survival (HR = 0.36, 95% CI: 0.13–0.98; p = 0.046)..Conclusions: Adjuvant radiotherapy is an effective and safe treatment modality for patients with stage I–III breast cancer, providing excellent locoregional control with a low incidence of treatment-related toxicities. Disease stage was an independent prognostic factor for disease-free survival.
Keywords: Breast cancer; adjuvant radiotherapy; locoregional recurrence; disease-free survival; overall survival.